Identification of a sensitive urinary biomarker, selenium-binding protein 1, for early detection of acute kidney injury. Issue 9 (3rd May 2017) - Kim, Kyeong Seok; Yang, Hun Yong; Song, Hosup; Kang, Ye Rim; Kwon, JiHoon; An, JiHye; Son, Ji Yeon; Kwack, Seung Jun; Kim, Young-Mi; Bae, Ok-Nam; Ahn, Mee-Young; Lee, Jaewon; et al.
ABSTRACT: Acute kidney injury (AKI) is associated with increased mortality rate in patients but clinically available biomarkers for disease detection are currently not available. Recently, a new biomarker, selenium-binding protein 1 (SBP1), was identified for detection of nephrotoxicity using proteomic analysis. The aim of this study was to assess the sensitivity of urinary SBP1 levels as an early detection of AKI using animal models such as cisplatin or ischemia/reperfusion (I/R). Sprague–Dawley rats were injected with cisplatin (6 mg/kg, once i.p.) and sacrificed at 1, 3, or 5 days after treatment. Ischemia was achieved by bilaterally occluding both kidneys with a microvascular clamp for 45 min and verified visually by a change in tissue color. After post-reperfusion, urine samples were collected at 9, 24, and 48 hr intervals. Urinary excretion of protein-based biomarkers was measured by Western blot analysis. In cisplatin-treated rats, mild histopathologic alterations were noted at day 1 which became severe at day 3. Blood urea nitrogen (BUN) and serum creatinine (SCr) levels were significantly increased at day 3. Levels of urinary excretion of SBP1, neutrophil gelatinase-associated lipocalin (NGAL), and a tissue inhibitor of metalloproteinase-1 (TIMP-1) were markedly elevated at day 3 and 5 following drug treatment. In the vehicle-treated I/R group, serum levels of BUN and SCr and AST activity were significantly increased compared to sham. Urinary excretion of SBP1 and NGAL rose markedly following I/R. The urinary levels of SBP1, NGAL, TIMP-1, and KIM-1 proteins excreted by AKI patients and normal subjects were compared. Among these proteins, a marked rise in SBP1 was observed in urine of patients with AKI compared to normal subjects. Based upon receiver-operator curves (ROC), SBP1 displayed a higher area under the curve (AUC) scores than levels of SCr, BUN, total protein, and glucose. In particular, SBP1 protein was readily detected in small amounts of urine without purification. Data thus indicate that urinary excretion of SBP1 may be useful as a reliable biomarker for early diagnosis of AKI in patients.